ASSESSING THE TECHNICAL EFFICIENCY LEVEL OF POULTRY EGG PRODUCERS IN ILORIN, KWARA STATE: A DATA ENVELOPMENT ANALYSIS APPROACH - N. A. Jatto; M. A. Maikasuwa; M. S.M. Jabo; U. I. Gunu (European Scientific Journal, ESJ, 2012)
Evidence had shown that the critical issue in poultry production in Nigeria is that of low production and inefficiency in resource allocation and utilization. Nowadays, chickens and eggs are regarded as comprehensive and favorite foods of people and they have a special place in food program of families. This study assesses the technical efficiency level of poultry egg producers in Ilorin, Kwara state using Data Envelopment Analysis. A stratified random sampling technique was adopted in selecting 150 poultry egg producers. The data for the study were collected with the use of well structured questionnaires from poultry farmers. The result showed the poultry egg farmers are relatively technically efficient in their use of resources, with a mean technical inefficiency of 26%. The mean input slack for numbers of birds, feeds and labour have slacks of 6.936, 91.021 and 0.334 respectively implying that inputs could be decreased by those units and still produce the same level of output. The study concluded that the poultry egg farmers are relatively technically efficient. The study recommend that reducing excess amount of inputs on one hand and raising output on the other hand, efficiency level can be improved and farmers could benefit economically.﻿